Half a century after the first bootprint on the lunar surface: the ichnological side of the Moon - Díaz Martínez, Ignacio (2021)
Humankind began with extra-planetary expeditions in the 1960s. To date, more than fifty manned and unmanned lunar missions have taken place. Maybe, the most iconic image of these campaigns is the bootprint left and photographed by the astronaut Edwin Aldrin. Nevertheless, there is also other evidence of human activities on the Moon, such as rover trails, drill holes, vehicles, and rubbish. For some researchers, ichnology only studies the traces made by one or several individuals with their own bodies, but other authors advocate that artefacts as well as traces made by these artefacts are also traces. In this context, the ichnology of the Moon allows both analysis of the traces left on the lunar surface themselves and discussion of the aim and scopes of ichnology. The Moon ichnology, which arises from the development of hominid ichnology, includes technical artefacts (called technofossils, e.g. Lunar Module, flag, religious text) and traces of technical artefacts (comprised in the new category technotraces, e.g. bootprints, drill holes) but not traces made by individuals with parts of their bodies. Although the lunar environment is very different from that of the Earth due to the absence of atmosphere, magnetic field, water, organic material and life, it is possible to propose three ichnological analogies between the Earth and its satellite. First of all, traces on the Moon surface are subjected to very slow sedimentation rates, similar to what occurs in abyssal bottoms or caves, among other environments. Moreover, physical and mechanical properties allow comparison with processes leading to the formation of traces in volcanic ash deposits with those acting on the soil and regolith of the Moon. Finally, cultural similarities have been identified between the traces left by humans on the Moon and comparable expeditions of humankind, such as Antarctica and the North Pole. The evolution of human technical artefacts has been used to help characterise the onset of the “Anthropocene”. These artefacts can be included within the technosphere and can also be thought to be phenotypic expressions of human genes. Therefore, the traces left on the Moon as well as others which are in other celestial bodies or even in the space, can be considered evidence of extended phenotype of Homo sapiens and the “Anthropocene” beyond the Earth.